Removal of foreign bodies from the tract upper digestive system by flexible endoscopy: Study of 75 cases - de Simone, Gustavo H; Boccardo, Carlos; Calleri, Daniel; Piazze, Alvaro; Zimmer, Walter (Cirugía del Uruguay, 1994)
A retrospective analysis of 75 cases of foreign bodies in the upper digestive tract treated by means of flexible endoscopy is carried out. lndications and advantages of the method as we/1 as the good results that are obtained are analysed.